Design of Psychomotor Domain Assessment Instruments in Indonesian Language Learning at Elementary Schools - Irawan, M. Ferry; Rizki, Nikentari; Noptario (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2023)
The characteristics of psychomotor skills include sensory skills, alertness, and the ability to act in a complex manner. The psychomotor skills of students in learning Indonesian can be seen from the students' proficiency in writing stories. This study aims to describe how to create a design and assessment instrument in the psychomotor domain in Indonesian language learning. The method used in this study is descriptive qualitative research with library research as the type of research. Based on the research method and type, the data sources are books and scientific articles related to the topic. The results of the study show that the design and assessment instrument in the psychomotor domain in Indonesian language learning can be done in the form of tests and non-tests. Test assessment instruments can be conducted when the learning process has taken place, and non-test instruments can be conducted while the process is ongoing, namely when students are practicing